HANOI - Valentin, Karen (Tidsskriftet Antropologi, 2003)
The article discusses the role that cities play in constructing and mediating particular historical accounts. Drawing on fieldwork experiences from Hanoi and Kathmandu it adopts a comparative perspective and explores how history is mediated, experienced and interpreted through the physical organisation of the city. History is conceptualised both chronologically as sequences of events that can be traced in the physical environment of the city and as a temporally specific narrative about the city and the wider society of which it is part. The article throws light on the impact different political regimes have had on the built environment and how this has informed the social organisation and human use of urban space in Hanoi. Comparing this with the social and physical organisation of Kathmandu two particular issues become salient, firstly the way in which the influence of foreign powers is physically manifest in the city; secondly how specific places, as national symbols of unity, frame everyday activities in the city.